Mechanical Safety Risk Analysis of Smart Factory. Issue 1 (April 2021) - Cheng, Zhou; Likai, Ju; Min, Cao; Xiangyan, Zhang
Abstract: In view of the mechanical safety risks of industrial robots, AGVs and other mobile devices that are widely used in smart factories, a mechanical safety risk analysis of smart factories method is carried out. First, it analyzes the mechanical safety risks of CNC machine tools, industrial robots, AGVs, and warehouses in smart factories. Then, a specific seal production workshop is taken as an example. It conducts a mechanical safety risk analysis and gives a safety plan to reduce the risk. The mechanical safety of the personalized seal workshop has achieved sufficient risk reduction. This article can provide a certain reference for conducting mechanical safety risk analysis during the construction of smart factories.